2008
DOI: 10.1254/jphs.sc0070374
|View full text |Cite
|
Sign up to set email alerts
|

Acute Protective Effects of Simvastatin in the Rat Model of Renal Ischemia-Reperfusion Injury: It Is Never Too Late for the Pretreatment

Abstract: Abstract. Acute pretreatment with a single i.v. bolus injection of simvastatin (1 mg / kg) significantly protects rat kidney injured by ischemia-reperfusion (I / R) (45 min + 6 h). We aimed to determine the optimal timing of such a pretreatment. The effects of both injections of simvastatin before ischemia and reperfusion were similar regarding total histological score. However, simvastatin injected 30 min before ischemia was 30% -75% more effective in reduction of serum creatinine levels and interstitial edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
3
15
0
3
Order By: Relevance
“…Pre-conditioning for 5 days with cerivastatin resulted in renal protection in mice subjected to iAKI (10) . In addition, the administration of simvastatin in a model of renal I/R resulted in a reduction in the area of acute tubular necrosis, which was confirmed by histological data and improvement in tubular function (11) . Studies have confirmed the power of statins as renoprotective agents due to their anti-inflammatory and antioxidant actions, two mechanisms that are significant in iAKI.…”
Section: Discussionsupporting
confidence: 52%
“…Pre-conditioning for 5 days with cerivastatin resulted in renal protection in mice subjected to iAKI (10) . In addition, the administration of simvastatin in a model of renal I/R resulted in a reduction in the area of acute tubular necrosis, which was confirmed by histological data and improvement in tubular function (11) . Studies have confirmed the power of statins as renoprotective agents due to their anti-inflammatory and antioxidant actions, two mechanisms that are significant in iAKI.…”
Section: Discussionsupporting
confidence: 52%
“…Sixty minutes of ischemia does not increase MDA levels, whereas 15 min of reperfusion results in a large increase in kidney lipid peroxidation and aggravates cell injury. 20,21 Hence, Bai administration 30 min before reperfusion can protect the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…32 Due to their antiinflammatory effects and protective role in preventing ischemia-reperfusion injury, it has been hypothesized that statins may provide beneficial effects in renal transplant recipients. 57 The one major randomized trial conducted on the effects of statins on renal transplant recipients was the ALERT (Assessment of Lescol in Renal Transplant) trial. 58 A total of 2,102 posttransplant patients were randomized to either 40 mg daily of fluvastatin or placebo, with a mean follow-up of 5 years.…”
Section: Statins and Renal Transplantmentioning
confidence: 99%